Design development and performance evaluation of waste plastic shredder - A. Raji, Nurudeen; S. Ojo, Seun; M. Hunvu, Sejero (Journal of Production Engineering, 2020)
The conservation of energy and sustaining a clean environment have been a focus of attention. Waste plastics release hazardous substances into the environment. Plastic shredding machines have played a considerable role in the waste plastic recycling process, addressing the problems associated with plastic waste and harnessing the significant energy potential that waste plastics can provide for human needs. In this paper, a 50 kg processing shredding machine for waste plastics was designed and fabricated. The drive mechanism for the machine combined both belt and gear drives to mitigate the deficiencies associated with common single belt drive shredders. Data obtained from the design analysis of the shredder machine were used to fabricate the machine, aiming to optimize the design parameters of the drive mechanisms for improved energy utilization of the prime mover. Performance evaluation of the machine indicates that it achieves an efficiency rating ranging between 90-96% for processing HDPE, PVC, and PET waste plastics.